Toward Strengthened EITI Reporting : Summary Report and Recommendations - Ravat, Anwar; Ufer, Andre (World Bank, Washington, DC, 2014)
This document draws on Extractive Industries Transparency Initiative (EITI) country implementation experience and contains the summary report and recommendations of a consultation process. The goal of the consultation process was to examine and recommend ways to strengthen EITI reporting by building on existing EITI policy guidance, while streamlining the reports and promoting qualitative improvements in disclosure within them. Accordingly, the recommendations in this document are addressed to the EITI International Secretariat and through it, to the EITI Board, as well as stakeholders in EITI-implementing countries.